High performance organic semiconducting device and physics - Qin, Fang (2010)
Organic semiconducting material-based organic electronics have extensively studied over the last twenty years. It offers several advantages over the traditional inorganic semiconductor technologies. First, organic electronics are compatible with low-cost mass manufacturing process such as direct printing, embossing and other solution-based processes, which make them favourable to applications in markets where cost is the key factor. Second, organic electronics can use a varietey of substrates including plastics for remarkable mechanical flexibility. Another distinguishing factor is the multiple functionalities that organic materials can sustain when synthesized with carefully designed chemical structures, which may allow the fabrication of multifunctional organic devices using extremely simple device structures.